Exploration of Agent of Change Perceptions on Health Education for Stunting Prevention Based on the Health Belief Model - Claudia Mel Kurniawan; Iha Nursolihah; Yosi Meidiawati (Journal of Hospital Management and Services, 2026)
Stunting is a chronic nutritional problem that hinders physical and cognitive growth. This qualitative study with an exploratory phenomenological design aims to explore the perceptions of GenRe Ambassadors of Karawang Regency regarding stunting prevention education based on the Health Belief Model (HBM). Through purposive sampling, five informants were involved in in-depth interviews which were analyzed using the Colaizzi thematic technique. The results of the study identified six main themes: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and educational efforts and expectations. The informants recognized the risk of stunting due to unhealthy lifestyles and a lack of reproductive readiness. Although education was considered effective in increasing awareness, the main barriers were found to be the low interest of adolescents and the negative influence of social media. The study concludes that adolescents have a crucial role as agents of change. Strengthening peer education and digital campaigns is highly necessary to effectively break the chain of stunting.